FACTORS INFLUENCING DEVELOPMENT OF GREEN WOMENS ENTREPRENEURSHIP IN SERBIA - Mitic, Nina; Srebro, Bosiljka; Popovic, Jovanka; Kvrgic, Goran; Dedjanski, Stevica (Economics of Agriculture, 2021)
Environmental demanding situations require businesses to innovative as a way to gain each environmental, economic and social goals. This article objectives to suggest the elements influencing improvement of green female entrepreneurship thinking about the improvement possibilities thru standardization and gender equality inherent within side the green economy. Using the methods of regression evaluation with the aggregate of Likerts scale approach, 226 woman entrepreneurs from Serbia in 2021 have been involved in the research. The findings display female entrepreneurship however also, that there may be inadequate interest been committed to them within side the procedure of greening their enterprise in green economy support measures for small and medium companies.